An investigation of challenges in the existing pattern of intra-city traffic in Enugu metropolis - Echendu, Ifeanyi F.; Okeke, Francis; Nnaemeka-Okeke, Rosemary C. (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Cities all over the world are characterized by a set of activities, which account for the concentration of people in them, achievable by means of transportation. However, this integral aspect of urban infrastructure face great challenge in most urban areas. This research examines the challenges in the existing pattern of intra-city traffic in Enugu metropolis. Six neighbourhood make up the study population drawn from three high, two medium and one low residential densities neighbourhoods based on stratified and simple random sampling technique. Data collection instrument were questionnaires administered to 400 respondents. The result of the study indicates that major travel mode within Enugu metropolis is mini buses and tricycles while commuters undergo stress during their trips regardless of the good condition of roads within the metropolis. Furthermore, it highlights traffic congestion during peak period and narrowness of most roads within the metropolis as the main challenge to existing pattern of intra-city traffic. It concludes and recommend for the re-introduction of Non-motorized transport mode of walking and cycling complemented by the Coal city public transit shuttles that once existed. It also advocates for policies that ensure decentralization of activity to reduce congestion and the need for daily travel.